A comparative study on the fatigue life of the vehicle body spot welds using different numerical techniques: Inertia relief and Modal dynamic analyses (Fracture and Structural Integrity, 2020)
Among different parts of a vehicle, the body is the main load-bearing component and as a result, its durability is critical. Fatigue analyses are typically divided into different categories, the quasi-static methods and the dynamic methods. The aim of this paper was to compare the inertia relief and modal dynamic approaches for their formulation, accuracy and computation time. The chosen case study is the fatigue life of the vehicle body. By utilizing multi-body dynamics model and driving the vehicle on different standardized roads and by different velocities, the force and moment time histories which act on the body were calculated and later used by the finite element model for the stress analysis. Then, by using the structural stress method, the fatigue life of the vehicle spot welds were calculated and the results were compared for both quasi-static and dynamic approaches. The findings reveal that the modal dynamic method is almost 37 times more time-consuming than the inertia relief approach, but if accuracy is desired, it can be up to 96% more accurate. Also as predicted, at low frequency loading (less than 10% of the first nonzero frequency of the structure), there is no difference between the results of both methods.
Keywords: Body-In-White; Inertia relief; Modal dynamic; Spot weld; Structural stress method